Allah, Budaya Populer dan Gamers:: Sebuah Respons Teologi Kristen Terhadap Tantangan Budaya Game Online - Rano Baki, Janter Efrata (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2025)
This study aims to explore the challenges posed by online gaming culture and how Christian theology responds to it in an objective manner. The research is qualitative, employing a literature review method, and specifically utilizes an interdisciplinary approach encompassing psychology, sociology, neuroscience, and Christian theology. The findings suggest that the challenges of online gaming culture indicate that Gamers experience a loss of self-control, emphasize hedonism and utilitarianism, social isolation, and damage to brain functions, particularly the prefrontal cortex, which is responsible for future planning, decision-making, and morality. In response, Christian theology contributes the concept of Deus Ludens, or the God who plays (Genesis 3), which does not oppose the activity of gaming itself but challenges the online gaming culture that has the potential to undermine humanity as the image of God (Imago Dei). The study introduces the concept of Homo Faber Religious-Ludens, which encourages Gamers to balance online gaming with responsible work. This contribution aids Gamers in restoring their identity as responsible images of God, by managing their time, gaming activities, and work in a sustainable manner.